Våtmarken i Fredriksdalsviken fungerar som en effektiv järn- och aluminiumsänka - Nilsson,Erik (2025)
Leakage of iron and aluminium from acid sulphate soils has received more and more recognition in Sweden during recent years. Research show that key drivers for this release of metals is lowered groundwater levels and aeration of sulphide soils which turns the soils into acidic sulphate soils. This can cause exstensive degradation of the surrounding environment which has been observed downstreams Helge å and around Fredriksdalsviken nature reserve in Kristianstad municipality. The aim of this study was to examine at the newly constructed wetland in Fredriksdalsviken and see how well it traps iron and aluminium, were most of the metal sedimentation occurs in the wetland, and how these metals are affected by pH, oxygen and water flow. The aim was also to look at what aquatic macroinvertebrates that manage to establish in the wetland. To achieve this, I took water samples every other week in the wetland during winter and spring. I measured pH, turbidity, oxygen saturation and water flow. To estimate sedimentationrates of iron and aluminium, I constructed an experiment in the laboratory with water from the inlet of the wetland were pH and oxygen levels were manipulated. I furthermore installed sedimentation traps in the different sedimentation basins. Once in a month I also collected aquatic macroinvertebrates with a mesh net in the inlet and the outlet of the wetland. The constructed wetland is an efficient sink for iron and aluminium and the concentrations decrease along the wetland. Sedimentation rates increased when pH was higher and sedimentation rates of iron also increases with higher oxygen saturation. Flow seems to play a vital role for the transport of metals with peak concentrations of iron during higher flows. Divirsity of aquatic macro invertebrates was low in the inlet and the outlet of the wetland, as indicated with low Shannon-Wiener index.